Time-dependent variation in immunoparalysis biomarkers among patients with sepsis and critical illness - Samuelsen, Abigail; Lehman, Erik; Burrows, Parker; Bonavia, Anthony S. (Frontiers in Immunology, 2024)
IntroductionImmunoparalysis is a state of immune dysfunction characterized by a marked reduction in the immune system’s responsiveness, often observed following severe infections, trauma, or critical illness. This study aimed to perform a longitudinal assessment of immune function over the initial two weeks following the onset of sepsis and critical illness.MethodsWe compared ex vivo-stimulated cytokine release from whole blood of critically ill patients to traditional markers of immunoparalysis, including monocyte Human Leukocyte Antigen (mHLA)-DR expression and absolute lymphocyte count (ALC). A total of 64 critically ill patients were recruited in a tertiary care academic medical setting, including 31 septic and 33 non-septic patients.ResultsWhile mHLA-DR expression significantly increased over time, this was primarily driven by the non-septic subset of critically ill patients. ALC recovery was more pronounced in septic patients. Ex vivo stimulation of blood from septic patients revealed significant increases in TNF and IL-6 production over time. However, interferon-gamma production varied depending on the ex vivo stimulant used, and after normalization of cytokine concentrations to lymphocyte counts, it did not show significant recovery over time from illness onset. No significant correlation was found between mHLA-DR expression and other immunoparalysis biomarkers.DiscussionThese findings suggest the need for more nuanced immune monitoring approaches beyond the traditional ‘sepsis’ versus ‘non-sepsis’ classifications in critically ill patients. Additionally, they provide further evidence of a potential window for targeted immunotherapy in the first weeks of critical illness.